Hubungan Perilaku Ibu Tentang Higenitas Botol Susu Dengan Kejadian Diare Pada Bayi Usia 6 - 24 Bulan di Klinik Pratama Mariana - Pardede, Debora Yolanda Octaviani; Raja GukGuk, Siti Nelly; Bate’e, Siska Yanti Niscahaya; Toruan, Krisnawati L; Silaban, Verawaty Fitrinelda (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to determine the relationship between maternal behavior regarding the hygiene of milk bottles and diarrhea in babies aged 6-24 months at the Pratama Mariana Clinic in 2023. The data collection method uses quantitative research with a cross-sectional plan. Data collection uses a questionnaire sheet. The statistical test used is chi-square. The research results showed that the results of the chi-square test obtained a p value of 0.000, meaning that there was a relationship between mothers' knowledge, attitudes and actions regarding the hygiene of milk bottles and the incidence of diarrhea in babies aged 6-24 months. In conclusion, the research results show that there is a relationship between maternal behavior regarding milk bottle hygiene and the incidence of diarrhea in babies aged 6-24 months. Keywords: Baby, Diarrhea, Milk Bottle Hygiene, Behavior